Development of Instrument for Improving Teaching Basic Skills through Microteaching - Mila Ermila Hendriyani; Dwi Ratnasari; Ika Rifqiawati (Gagasan Pendidikan Indonesia, 2020)
Microteaching activities are part of the course of Teaching Competence Development. This course is designed to equip students with basic teaching skills, teacher competence, teacher / educator ethics, and teaching practice (microteaching). This research used descriptive method for identification and analysis of micro teaching instrument based on lecturer appraisal and peer assessment of student followed by development method (Research And Development). The micro teaching assessment instrument currently used does not include the basic teaching skills aspects a teacher must possess. Therefore, in this research, the development of micro teaching assessment instrument in the course of Teaching Competence Development is based on basic teaching skill to improve teaching skill for biology teacher candidate. The result of instrument analysis by the experts found that on the aspect of Basic Teaching Skills obtained the value of 89.06, the aspect of the language 100, and the evaluation aspect 100. The results of the calculation of both experts averaged and obtained the value of the feasibility of 91.25%. These results indicate that the product of the Micro Teaching Instrument based on the Basic Teaching Skills developed into the category is very feasible.